Health-related quality of life and psychological distress among adults in Tanzania: a cross-sectional study - Olena Ivanova; Tembeka Sineke; Rebekka Wenzel; Elimina Siyame; Julieth Lalashowi; Abhishek Bakuli; Fidelina Cumbe Zekoll; Michael Hoelscher; Andrea Rachow; Denise Evans; Issa Sabi; Nyanda Elias Ntinginya (BMC, 2022)
Abstract Background Little data is available on health-related quality of life (HRQoL) and mental health of the general population in Tanzania. We aimed to describe HRQoL and level of psychological distress among adults in Mbeya and Songwe Regions of Tanzania. Methods We conducted a cross-sectional study between April and October 2019 in Mbeya and Songwe Regions. Data were collected using the Medical Outcomes Short Form-36 (SF-36) questionnaire and the Page Kessler Psychological Distress Scale (K10). We described demographic characteristics of participants and used log-binomial regression to identify participant characteristics associated with psychological distress (K10 score ≥ 20). Results A total of 393 adults were enrolled. The participants had a median age of 29 years (IQR 23-40) and 54.2% were male. Participants reported a physical component summary score (PCS) with a mean of 54.7 (SD7.1) and a mental component summary score (MCS) with a mean of 55.5 (SD5.1). Older participants (≥ 40 year) and those that were divorced/widowed reported lower physical functioning, energy/vitality and emotional well-being compared to their counterparts (p < 0.05). In terms of psychological distress, majority of participants (78.4%; 305/389) reported that they were likely to be well (K10 score < 20), while 13.4% (52/389) reported to have mild (K10 score 20-24), 5.7% (22/389) moderate (K10 score 25-29), and 2.6% (10/389) severe (K10 score ≥ 30) psychological distress. Conclusions Physical function and mental well-being in this adult population from Tanzania were lower than that reported in other similar research in Tanzania and other African countries. This study provides valuable references for other research initiatives and clinical services in this region.